Library Logging System Design Based on Radio Frequency Identification Interface using Arduino Uno board as Platform - Morallo, Narcisa (JPAIR Multidisciplinary Research, 2018)
Radio Frequency Identification (RFID) technology revolutionizes the automatic identification of objects. In this paper, library logging system based on radio frequency identification (RFID) interface using Arduino Uno board as platform is proposed and prototyped. Technology in Arduino and RFID are reviewed. RFID MFRC522, is a highly integrated reader/writer IC for contactless communication at 13.56 MHz. RFID technology uses electromagnetic fields to transfer data to automatically identify objects. Information of books with RFID tags are registered in the database system. When books are scanned in the RFID reader, the system will automatically give the information of the book and the current date and time. User will input the borrowers’ information which will automatically login into the system with the book details. Arduino microcontroller is used as a micro web server and a communications gateway among hardware modules. Design shows that RFID interfacing using Arduino Uno board as platform can make library logging system more efficient and convenient through the automation of workflow processes. To reduce library losses, security and item identification should be combined in a single tag in future designs.